ANALISIS MINAT BERWIRAUSAHA YANG TIDAK MELANJUTKAN PENDIDIKAN OLEH GURU BIMBINGAN KONSELING KELAS XI SMA - Ardiansyah, Andri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aims to analyze the interests of entrepreneurship for those who do not continue the education provided by guidance and counseling teachers in SMA Negeri 10 Pontianak The method used is descriptive method and the form of research is the form of survey research. The population in this study is 120 and the sample is 50 students in SMA Negeri 10 Pontianak. This research uses quantitative method. Data collection techniques used are direct communication in the form of interviews and indirect communication in the form of questionnaires. While the technique of data analysis using the formula percentage.Based on the results of this research, information service on entrepreneurship interest has reached the score in the